2014
DOI: 10.1038/jp.2014.146
|View full text |Cite
|
Sign up to set email alerts
|

Lower vitamin D levels are associated with increased risk of early-onset neonatal sepsis in term infants

Abstract: Lower maternal and neonatal 25-OHD levels are associated with EOS. These data suggest that adequate vitamin D supplementation during pregnancy may be helpful to prevent EOS in term neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 39 publications
9
93
2
6
Order By: Relevance
“…18,38,39 In a recent study of our group, we demonstrated that lower maternal and neonatal 25-OHD levels were associated with early-onset sepsis in term infants. 40 In a very recent study, VDR Fok 1 polymorphism was found to be associated with increased frequency of BPD. 41 Our study is the first in the literature to demonstrate a possible association between maternal/neonatal 25-OHD levels and BPD.…”
Section: Discussionmentioning
confidence: 98%
“…18,38,39 In a recent study of our group, we demonstrated that lower maternal and neonatal 25-OHD levels were associated with early-onset sepsis in term infants. 40 In a very recent study, VDR Fok 1 polymorphism was found to be associated with increased frequency of BPD. 41 Our study is the first in the literature to demonstrate a possible association between maternal/neonatal 25-OHD levels and BPD.…”
Section: Discussionmentioning
confidence: 98%
“…For the entire group of 50 infants with early-onset neonatal sepsis (EONS), the postpartum maternal and neonatal 25(OH)D levels were 56 nmol/l (SD = 17 nmol/l), compared with 91 nmol/l (SD = 5 nmol/l) and 45 nmol/l (SD = 12 nmol/l) respectively for the controls [Cetinkaya et al 2015a]. A second study in Turkey involving 40 neonates with EONS and 43 controls found that cord blood 25(OH)D levels were 32 nmol/l (8-197 nmol/l) for those with EONS and 53 nmol/l (13-295 nmol/l) for controls, p = 0.04 [Cizmeci et al 2015].…”
Section: Maternal Hypovitaminosis D Impact On Neonatal Infections Andmentioning
confidence: 99%
“…59,60 One of these studies only included patients with culture-proven sepsis, while the other did not find significant associations in the subset of cases with culture-proven sepsis. The Gad et al 61 study similarly found lower cord 25(OH)D levels in subjects with neonatal pneumonia compared with healthy controls.…”
Section: Infectious Diseasementioning
confidence: 99%